Halal soap enriched with clay for cleansing purposes - Kunram, Kamariya; Kunram, Romah; Wongwailikhit, Kanda (Iraqi Journal of Science, 2025)
Two varieties of halal soaps—body and laundry—were developed by incorporating various types of clays to effectively cleanse severe najis (impurities) in adherence to Islamic principles. Four clays-kaolin, white clay, bentonite, and clay loam, were tested individually at concentrations ranging from 5% to 20% w/w. Selection of the optimal formulation was based on physical, chemical, and sensory characteristics. The results indicated that a 20% w/w concentration of kaolin clay was the most suitable for both soap types. At this composition, the soap provided an appropriate pH, strong foam production, and foam stability, meeting most requirements for industrial soap standards. Both body and laundry soaps enriched with kaolin received high satisfaction ratings for cleanliness and non-irritation. The incorporation of kaolin in soap, along with its high pH, exhibited bactericidal effects against both Staphylococcus aureus and Escherichia coli. The turbidity of the soap solution confirmed the presence of clay particles during use. In conclusion, the halal soap formulations align with religious cleansing requirements and suit the lifestyle of modern consumers worldwide.